Tingkat Kesadaran Pedagang Terhadap Peraturan Ketentuan Tertib Niaga - Budi Yasri (Musamus Journal of Public Administration, 2020)
Trade is an important thing in social life. Therefore, regulations are made to support the safety and comfort aspects of both the seller and the buyer. These regulations include the UUML (Legal Metrology Law), the UUPK (Consumer Protection Act), and PP LIP (Government Regulations for Food Advertising Labels). To find out how successful these regulations can be assessed from the public's knowledge of the regulations that have been enacted. How much knowledge of the rules can be obtained from interviews conducted in the community. With interviews, it can be seen how successful the regulations were made both in quantity and quality. From the interviews, it was obtained that 50% of the public already knew and implemented the regulation.